Accelerating Economic Value In Developing Regions: A Meta Synthesis Of AI Adoption In Indonesian Smes And Implications For North Sulawesi's Digital Ecosystem - Taroreh, Stefen R. A.; Makhfudi; Wahyuningsih; Wasilu, Irfan H. (Asia Pacific Journal of Interdisciplinary Studies, 2025)
The integration of Artificial Intelligence (AI) into Small and Medium Enterprises (SMEs) offers a pathway to economic acceleration, yet a significant "digital divide" persists in developing archipelagic regions. This study aims to bridge the gap between foundational digitization and advanced AI-driven value creation by constructing a strategic roadmap specifically for the North Sulawesi digital ecosystem. The research employs a qualitative meta-synthesis design, systematically analyzing 22 peer-reviewed empirical studies published between 2021 and 2025. Data were extracted from high-quality national journals (SINTA-indexed) and synthesized using the Technology-Organization-Environment (TOE) framework to map technological patterns, organizational capabilities, and environmental pressures. The synthesis reveals a critical "adoption dichotomy" within the Indonesian landscape. While national-level data indicate a shift toward predictive analytics and automation, North Sulawesi’s SMEs remain situated in the "onboarding" phase, characterized by reliance on transactional tools (QRIS) and static social media profiling. The analysis identifies organizational readiness—specifically human capital and digital literacy—as the primary mediator determining whether technological adoption translates into measurable business performance. Furthermore, existing policy frameworks focused solely on infrastructure are deemed insufficient for advanced AI integration. To accelerate economic value, regional stakeholders must pivot from a provider-centric model to an enabler-centric approach. The study proposes a holistic framework that prioritizes subsidized digital upskilling and the establishment of regional regulatory sandboxes. These interventions are essential to mitigate resource constraints and facilitate the transition from simple digitization to intelligent economic resilience in developing regions.